The Role Of Corporate Social Responsibility In Improving Work Engagement Through Employee Well Being: Implications For SDGs In The Manufacturing Industry In Surabaya - Nur Pradani, Siska Putri (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) on work engagement through employee well-being in the manufacturing industry in Surabaya. A quantitative approach was employed by collecting data through employee surveys, which were analyzed using PLS-SEM path analysis to examine causal relationships among variables. The results indicate that CSR positively influences employee well-being. Furthermore, employee well-being fully mediates the relationship between CSR and work engagement, while the direct effect of CSR on work engagement is not significant. These findings highlight that CSR programs initiatives are more effective in fostering engagement when they enhance employees’ physical, psychological, and social conditions. Practically, this study suggests that effective CSR implies that well-targeted CSR implementation can strengthen productivity and innovation capacity while also supporting sustainable development through improved employee health, decent work, economic growth, and human capital development.